Acceptance, Social Preparation, and Psychoeducation: Autistic Young Adults’ Recommendations for Transition to Adulthood - Wolpe, Samara M.; Lee, Maxwell N.; Koenig, Jamie; Tien, Ingrid; McLean, Kiley (Journal of autism and developmental disorders, 2025)
Little research has explored the experiences of autistic adults retroactively recalling the preparation they did (or did not) receive for adulthood. The current study explores autistic young adults' experiences transitioning into the responsibilities and challenges of adulthood through semi-structured interviews. Seventeen autistic adults were interviewed (M =26.7 years). Themes related to preparation for transitioning into adulthood from high schools and families were analyzed. Data analysis was conducted through the theoretical frameworks of the Social Model of Disability (Oliver, 1990) and Transition Theory (Schlossberg, 1981). Reflexive thematic analysis (Braun & Clarke, 2024a, b) was used. Participants relayed Constructive Experiences surrounding Study Strategies, Mentorship, and Learning Life Skills in preparing them self-sufficiency in adulthood, the Destructive Experiences of Discouragement and Insults from people in positions of authority and forced Suppression of their authentic selves. Participants recalled being Underestimated and Infantilized. Participants suggested that high schools offer specific Social Preparation, emphasizing Study Skills and Family Involvement in transition preparation, and offering Psychoeducation to families. Lastly, participants suggested that families practice Understanding, Acceptance, Honesty, and offer Support for Executive Functioning. This work builds on prior research of autistic individuals' experiences by primarily focusing on preparation for employment and postsecondary education, in addition to providing primarily recommendations for how preparation services can be improved. The results from this study provide guidance on next steps for improving transition-related resources for autistic teens, families, and high schools in preparing for this critical next stage in life.